Effects of copper sulfate, zinc oxide, and neoterramycin on weanling pig growth and antibiotic resistance rate for fecal Escherichia coli - N W Shelton; M E Jacob; Michael D Tokach; Joel M DeRouchey; R G Amachawadi; X Shi; Tiruvoor G Nagaraja; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
A total of 180 weanling pigs (PIC TR4 ×1050, initially 11.1 lb and 21 d of age) were used in a 42-d growth trial to compare the effects of supplemental zinc, copper, and in-feed antimicrobial on weanling pig growth and antibiotic resistance of fecal Escherichia coli. There were 5 dietary treatments with 6 pens per treatment and 5 pigs per pen. Pens were assigned to dietary treatments in a randomized complete block design. Treatments were arranged in a 2 × 2 factorial design with main effects of copper sulfate (0 or 125 ppm) and zinc oxide (0 or 3,000 ppm for 14 d and 0 or 2,000 for 28 d). The fifth treatment was in-feed antimicrobial (50 g/ton neomycin sulfate and 50 g/ton oxytetracycline HCl). All diets were supplemented with165 ppm zinc and 16.5 ppm copper from the trace mineral premix. Fecal samples were collected from 3 pigs per pen on d 14 and 42 to determine total coliform and E. coli counts as well as E. coli antibiotic resistance rates. Pigs fed added zinc oxide had increased (P<0.04) ADG and tended to have improved (P<0.09) ADFI and F/G from d 0 to 14. From d 14 to 42, pigs fed added zinc oxide had poorer (P<0.007) F/G than those with no added zinc oxide, and pigs fed added copper sulfate had improved (P<0.07) F/G compared with those fed no added copper sulfate. Over the entire 42-d trial, a trend for a copper × zinc interaction was detected (P<0.09) for ADG as pigs fed the addition of copper sulfate or zinc oxide had increased ADG over the control; however, when zinc and copper were combined, growth rate was similar to that when each was added singularly. Therefore, no additive effects were observed in this experiment from feeding a combination of high levels of dietary copper and zinc. Dietary addition of copper sulfate, zinc oxide, or in-feed antibiotic had no effect (P>0.22) on total coliform or E. coli concentrations on d 14 or 42. For d-14 isolates, zinc supplementation had no effect (P>0.43) on E. coli resistance rate to chlortetracycline, neomycin, oxytetracycline, or tiamulin; however, copper supplementation tended to increase (P<0.10) resistance to chlortetracycline and oxytetracycline. A copper × zinc interaction was detected (P<0.02) for E. coli resistance to chlortetracycline and neomycin from isolates on d 42. These interactions were related to a significant decrease in resistance when copper sulfate was fed alone. High levels of zinc oxide improved performance in the early postweaning period, whereas high levels of copper sulfate offered numeric advantages in the later phase. Although the resistance rate varied with dietary treatment, no clear pattern was detected.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Bacterial sensitivity; Copper; Zinc; Swine